The Muslim legal system and its compatibility with fundamental rights - Bouroncle, Mauricio (2021)
The Muslim law of personal nature of faith-based, unlike other attached to theistic legal system it was from his first moment of existence, ie legal systems, is a right which applies only preaches by those human beings who are 1 integrated into the community of believers, in other words only applies to those with this religion or in principle it should be. This explains why they have an intimate connection with the religious sphere that turns the legal phenomenon in a subordinate and dependent on that categorys the rightis conceived as a part of religion. On the other hand fundamental rights or human rights are rights inherent in every human person by the simple fact that these taxes are virtually all states since the end of World War II and were enacted, and now are in positivised the certain specific legal systems.